The Effect of Distance to Health Care Facilities on Tuberculosis Treatment Compliance in Tuberculosis Patients: A Meta-Analysis - Rizki Aqsyari; Hendra Dwi Kurniawan; Safaruddin Safaruddin (Media Ilmiah Kesehatan Indonesia, 2026)
Patient adherence to tuberculosis (TB) treatment is an essential factor in ensuring therapeutic success, preventing relapse, and mitigating the rate of drug resistance in the community. One structural barrier frequently associated with suboptimal adherence levels is the geographical distance between the patient's residence and healthcare facilities. Given that previous literature still exhibits variations in empirical findings, this study aims to quantitatively synthesize and estimate the magnitude of the effect of healthcare facility distance on the treatment adherence of TB patients. This systematic review and meta-analysis was designed in adherence to the standard Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search strategy focused on the Google Scholar database by establishing inclusion criteria based on the PICO framework: TB patients (Population), easily accessible healthcare facilities (Exposure), inaccessible healthcare facilities (Comparator), and the level of treatment adherence (Outcome). Statistical synthesis was executed using Review Manager 5.3 software. The eligibility evaluation identified three case-control primary studies included in the analysis. The forest plot visualization confirmed that patients facing inaccessible healthcare facilities possess a significantly higher probability of non-adherence by 3.76 times compared to patients with easy access (aOR = 3.76; 95% CI = 2.11–6.70; p = 0.0001). Although the statistical test demonstrated perfect methodological homogeneity across the studies (I² = 0%), an indication of potential publication bias was detected through the funnel plot visualization. In conclusion, geographical distance barriers are proven to significantly degrade TB treatment adherence. Proactive policy interventions, such as service decentralization and community-based medical governance innovations, are highly crucial to overcome these spatial obstacles.